Answer:
<u>Cities A and B are 1,125 miles apart</u>
Step-by-step explanation:
1. Let's review the information given to us to answer the question correctly:
Distance between A and B in the map = 5 inches
Distance between C and D in the map = 4 inches
Actual distance between C and D = 900 miles
2. How many miles apart are cities A and B?
We will solve the question, using Direct Rule of Three, as follows:
Distance in the map Actual distance
A - B 5 inches x
C - D 4 inches 900 miles
***************************************************
4x = 900 * 5
4x = 4,500
x = 4,500/4
x = 1,125 miles
<u>Cities A and B are 1,125 miles apart</u>
Answer Z = -1/4
Step-by-step explanation:
-1/3+2z= -5/6
Add 1/3 to both sides
-1/3+2z+1/3 = -5/6+1/3
Simplify
2z=-1/2
Divide both sides by 2
2z/2 = -1/2/2
Simplify
z = -1/4
confused as to what you want but if you want to see the number then its 200,025
Answer:
See Below
Step-by-step explanation:
We are given 3 equations.
3x + 8
5x - 20
and
5x + 4y
First lets solve for x using the first two
3x + 8 = 5x -20
Move the variables to one side
3x + 8 = 5x -20
-3x -3x
8 = 2x -20
+20 +20
28 =2x
28/2 =2x /2
14 = x
Now we have x = 14
Lets plug this into the second equation to solve for the angle
3(14) + 8
42 + 8 = 50
5(14) - 20
70 - 20 =50
Now, lets plug the x and the angle into the third equation to find y
5 (14) +4y = 50
70 + 4y = 50
-70 -70
4y = -20
4y/4 = -20/4
y = -5
So now we have:
x = 14
y = -5
and the angle = 50
Hope this helps!
9514 1404 393
Answer:
D.) a+2b
Step-by-step explanation:
The integers 'a' and 'b' can be any, so you can choose a couple and evaluate these expressions to see what you get. For example, we can let a=1 and b=0. For these values, the offered expressions evaluate to ...
A) 3(0) = 0 . . . even
B) 1 +3 = 4 . . . even
C) 2(1+0) = 2 . . . even
D) 1 +2(0) = 1 . . . odd
_____
<em>Additional comment</em>
These rules apply to even/odd:
- odd × odd = odd
- odd × even = even
- even × even = even
- odd + odd = even
- odd + even = odd
- even + even = even
Then A is (odd)(even) = even; B is (odd)+(odd) = even; C is (even)(whatever) = even; D = (odd)+(even) = odd.